Interactions between chloroplast and mitochondrial genomes in 11 Salix species - Kim, Yeseul; Jeong, Sumin; Baasanmunkh, Shukherdorj; Kim, Youngmoon; Choi, Hyeok Jae; Park, Inkyu (Frontiers in Plant Science, 2025)
IntroductionThe genus Salix, widely distributed across the Northern Hemisphere, is characterized by its dioecious nature and frequent natural hybridization. It has significant ecological and economic value in landscaping, ornamentation purposes, biomass production, and traditional medicine. Understanding its evolutionary dynamics is crucial for effective conservation and sustainable utilization. While hybridization and intracellular gene transfer offer valuable insights into its genetic architecture and evolutionary trajectories, studies examining both chloroplast and mitochondrial genomes remain limited.MethodsWe sequenced and assembled the chloroplast and mitochondrial genomes of male and female individuals from three closely related Salix species, namely S. pierotii, S. babylonica, and S. pseudolasiogyne, and incorporated data from eight additional Salix species for comparative analysis. Phylogenetic relationships were reconstructed and divergence times were estimated to elucidate the evolutionary history.ResultsThe chloroplast genomes ranged from 155,688 to 155,695 bp, and the mitochondrial genomes from 705,072 to 705,179 bp, both showing similar proportions of repetitive sequences. Phylogenetic analyses revealed two main clades corresponding to the Salix and Vetrix subgenera, with an estimated divergence time of approximately 25–26 MYA. Discrepancies between chloroplast- and mitochondrial-based phylogenies suggest distinct evolutionary histories, and certain mitochondrial genes showed stronger positive selection than chloroplast genes. Homologous fragments between the two organelle genomes indicate intracellular gene transfer events.DiscussionThe observed alternation between S. pierotii and S. pseudolasiogyne in the mitochondrial phylogeny may indicate potential gene flow or introgressive hybridization, providing further evidence of complex genomic interactions underlying the diversification of Salix. Overall, this study underscores the importance of mitochondrial genome analysis in revealing organelle genome evolution and its role in shaping genetic diversity and evolutionary dynamics within Salix.